Episiotomy During Vaginal Delivery: A Comparative Study at A Tertiary Facility in Nigeria - Grace G. Ezeoke; Olumuyiwa A. Ogunlaja; Tola Y. Bakare; Adegboyega A. Fawole; Abiodun S. Adeniran (AlQalam Journal of Medical and Applied Sciences, 2023)
Background an aim. The use of episiotomy to aid vaginal deliveries remains a common obstetric practice although the evidence remains inconclusive. However, its restrictive use has been recommended especially to reduce potential maternal or neonatal morbidities. The study compares the outcome of vaginal deliveries aided with and without episiotomy. Methods. This was a comparative study conducted at a tertiary facility with a policy of restrictive episiotomy. Participants were women who had vaginal delivery after 28 weeks gestation categorized into those who delivered with (case) or without episiotomy (control) over a ten-year period. Data source was the hospital delivery records and analysis was with SPSS version 24.0; p-value <0.05 was significant. Results. The prevalence of episiotomy was 37.8%, 43.5% of nullipara and 48.4% of teenagers had episiotomy while episiotomy use decreased with increasing parity. Episiotomy use was significantly higher for preterm delivery (p=0.001) and operative vaginal deliveries (ventouse [p=0.001], forceps [p=0.035]). its use was associated with higher primary postpartum hemorrhage (p=0.001) but lower incidence of perineal laceration (p=0.001). The odds for neonatal intensive admission were higher following episiotomy-assisted deliveries (OR2.92; 95%CI 2.586 – 3.297); perinatal mortality rate was 81/1000 versus 136/1000 live birth with or without episiotomy. Conclusion. The study supports the use of episiotomy during vaginal delivery especially for preterm and instrumental vaginal deliveries; however, institutions should prioritize compliance with standard care to further reduce the rate.